Volumetric modulated arc therapy treatment planning of thoracic vertebral metastases using stereotactic body radiotherapy. (19th January 2018) - Mallory, Matthew; Pokhrel, Damodar; Badkul, Rajeev; Jiang, Hongyu; Lominska, Christopher; Wang, Fen
Abstract: Purpose/Objectives: To retrospectively evaluate the plan quality, treatment efficiency, and accuracy of volumetric modulated arc therapy (VMAT) plans for thoracic spine metastases using stereotactic body radiotherapy (SBRT). Materials/Methods: Seven patients with thoracic vertebral metastases treated with noncoplanar hybrid arcs (NCHA) (1 to 2 3D‐conformal partial arcs +7 to 9 IMRT beams) were re‐optimized with VMAT plans using three coplanar arcs. Tumors were located between T2 and T7 and PTVs ranged between 24.3 and 240.1 cc (median 48.1 cc). All prescriptions were 30 Gy in 5 fractions with 6 MV beams treated using the Novalis Tx linac equipped with high definition multileaf collimators (HDMLC). MR images were fused with planning CTs for target and OAR contouring. Plans were compared for target coverage using conformality index (CI), homogeneity index (HI), D90, D98, D2, and Dmedian. Normal tissue sparing was evaluated by comparing doses to the spinal cord (Dmax, D0.35, and D1.2 cc), esophagus (Dmax and D5 cc), heart (Dmax, D15 cc), and lung (V5 and V10). Data analysis was performed with a two‐sided t‐test for each set of parameters. Dose delivery efficiency and accuracy of each VMAT plan was assessed via quality assurance (QA) using a MapCHECK device. The Beam‐on time (BOT) was recorded, and a gamma index was used to compare dose agreement between the planned and measured doses. Results: VMAT plans resulted in improved CI (1.02 vs. 1.36, P = 0.05), HI (0.14 vs. 0.27, P = 0.01), D98 (28.4 vs. 26.8 Gy, P = 0.03), D2 (32.9 vs. 36.0 Gy, P = 0.02), and Dmedian (31.4 vs. 33.7 Gy, P = 0.01). D90 was improved but not statistically significant (30.4 vs. 31.0 Gy, P = 0.38). VMAT plans showed statistically significant improvements in normal tissue sparing: Esophagus Dmax (22.5 vs. 27.0 Gy, P = 0.03), Esophagus 5 cc (17.6 vs. 21.5 Gy, P = 0.02), and Heart Dmax (13.1 vs. 15.8 Gy, P = 0.03). Improvements were also observed in spinal cord and lung sparing as well but were not statistically significant. The BOT showed significant reduction for VMAT, 4.7 ± 0.6 min vs. 7.1 ± 1 min for NCHA (not accounting for couch kicks). VMAT plans demonstrated an accurate dose delivery of 95.5 ± 1.0% for clinical gamma passing rate of 3%/3 mm criteria, which was similar to NCHA plans. Conclusions: VMAT plans have shown improved dose distributions and normal tissue sparing compared to NCHA plans. Significant reductions in treatment time could potentially minimize patient discomfort and intrafraction movement errors. VMAT planning for SBRT is an attractive option for the treatment of metastases to thoracic vertebrae, and further investigation using alternative fractionation schedules is warranted.